Acyl-CoA synthetase 4 modulates mitochondrial function in breast cancer cells - Benzo, Yanina (2024)
Mitochondria are dynamic organelles that respond to cellular stress through changes in global mass, interconnection, and subcellular location. As mitochondria play an important role in tumor development and progression, alterations in energy metabolism allow tumor cells to survive and spread even in challenging conditions. Alterations in mitochondrial bioenergetics have been recently proposed as a hallmark of cancer, and positive regulation of lipid metabolism constitutes one of the most common metabolic changes observed in tumor cells. Acyl-CoA synthetase 4 (ACSL4) is an enzyme catalyzing the activation of long chain polyunsaturated fatty acids with a strong substrate preference for arachidonic acid (AA). High ACSL4 expression has been related to aggressive cancer phenotypes, including breast cancer, and its overexpression has been shown to positively regulate the mammalian Target of Rapamycin (mTOR) pathway, involved in the regulation of mitochondrial metabolism genes. However, little is known about the role of ACSL4 in the regulation of mitochondrial function and metabolism in cancer cells. In this context, our objective was to study whether mitochondrial function and metabolism, processes usually altered in tumors, are modulated by ACSL4 in breast cancer cells. Using ACSL4 overexpression in MCF-7 cells, we demonstrate that this enzyme can increase the mRNA and protein levels of essential mitochondrial regulatory proteins such as nuclear respiratory factor 1 (NRF-1), voltage-dependent anion channel 1 (VDAC1) and respiratory chain Complex III. Furthermore, respiratory parameters analysis revealed an increase in oxygen consumption rate (OCR) and in spare respiratory capacity (SRC), among others. ACSL4 knockdown in MDA-MB-231 cells led to the decrease in OCR and in SCR, supporting the role of ACSL4 in the regulation of mitochondrial bioenergetics. Moreover, ACSL4 overexpression induced an increase in glycolytic function, in keeping with an increase in mitochondrial respiratory activity. Finally, there was a decrease in mitochondrial mass detected in cells that overexpressed ACSL4, while the knockdown of ACSL4 expression in MDA-MB-231 cells showed the opposite effect. Altogether, these results unveil the role of ACSL4 in mitochondrial function and metabolism and expand the knowledge of ACSL4 participation in pathological processes such as breast cancer.